Expression Status and Prognostic Significance of Gamma-Glutamyl Transpeptidase Family Genes in Hepatocellular Carcinoma - Tian, Shan; Li, Jiao; Guo, Yingyun; Dong, Weiguo; Zheng, Xin (Frontiers in Oncology, 2021)
Purpose Gamma-glutamyl transpeptidase (GGT) family genes play crucial roles in the formation and progression of several solid tumors. However, the expression patterns and the prognostic significance of GGT members in hepatocellular carcinoma (HCC) remain unknown. This study was designed to determine the expression profiles of GGT family members in HCC and validate the prognostic value of serum GGT protein in patients with HCC. Method We comprehensively searched public resources based on the LIHC dataset to determine the expression patterns, prognostic significance, DNA methylation status, immune infiltration, and biological pathways of GGT family genes in HCC. Subsequently, we validated the prognostic value of serum GGT protein in 85 patients with early-stage HCC subjected to curative hepatectomy from the Renmin Hospital of Wuhan University. Results Except for GGT1, other GGT family members (GGT5, GGT6, and GGT7) were found to be differentially expressed in primary HCC samples (N = 371) and normal control tissues (N = 50). Furthermore, a positive relationship was not only observed between GGT1 and GGT5 (Spearman coefficient: 0.24, P = 5.143 × 10−6) but also between GGT5 and GGT6 (Spearman coefficient: 0.38, P = 1.24 × 10−13). The expression of GGT1, GGT5, and GGT7 was correlated with overall survival (OS), and GGT7 was associated with disease-free survival (DFS) in patients with HCC. Negative associations between DNA methylation and expression of mRNA were observed for GGT1 (Spearman coefficient: −0.38, P = 6.24e-14), GGT6 (Spearman coefficient: −0.29, P = 1.23e-8), and GGT7 (Spearman coefficient: −0.34, P=6.7e-11). GGT family genes were well correlated with the infiltration levels of immune cells in HCC, especially CD4+ T cells, macrophages, and dendritic cells. Finally, when validated with clinical data from the Renmin cohort, a high expression of serum GGT protein was identified as a strong prognostic element of unfavorable OS (HR = 3.114, P = 0.025), but not of DFS (HR = 1.198, P = 0.05) in patients with HCC subjected to curative hepatectomy. Conclusion To our knowledge, this is the first comprehensive analysis of the expression patterns and clinical value of GGT family genes in patients with HCC. Our study laid the foundation for the clinical application of the GGT protein in the survival assessment of patients with HCC.